1994
DOI: 10.1111/j.1528-1157.1994.tb02440.x
|View full text |Cite
|
Sign up to set email alerts
|

Arylsulfatase A Pseudodeficiency and Lafora Bodies in a Patient with Progressive Myoclonic Epilepsy

Abstract: Since age 12 years, a 25-year-old woman had a syndrome with myoclonic epilepsy, cerebellar signs, and spontaneous myoclonus. Skin biopsy showed typical Lafora bodies (LB), but she lacked a progressive course and mental impairment, hallmarks of Lafora disease. Lysosomal enzyme assays showed low level arylsulfatase A (ASA) activity. DNA study disclosed a homozygous ASA Pd genotype. Both parents carried one Pd allele. The still-unknown relationship between the pathologic level of ASA activity and myoclonic epilep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Interestingly, it has been reported that in cobalt epilepsy the acid phosphatase activity in rat brain was significantly elevated (4). By contrast, in the skin biopsy samples and in the leukocytes from epileptic patients the arylsulfatase A activity decreased (5,6). In kainateevoked seizures, the levels of cathepsin D mRNA in rat brain were found to be elevated (7).…”
Section: Introductionmentioning
confidence: 85%
“…Interestingly, it has been reported that in cobalt epilepsy the acid phosphatase activity in rat brain was significantly elevated (4). By contrast, in the skin biopsy samples and in the leukocytes from epileptic patients the arylsulfatase A activity decreased (5,6). In kainateevoked seizures, the levels of cathepsin D mRNA in rat brain were found to be elevated (7).…”
Section: Introductionmentioning
confidence: 85%
“…It may be worthwhile both to screen DNA from our patients for mutations in other genes known to be associated with early onset myoclonic epilepsy, including cystatin B and laforin, and to screen patients with myoclonic epilepsy for glucocerebrosidase deficiency. Of note, several different lysosomal storage disorders, including late-onset GM 2 gangliosidosis, GM 1 gangliosidosis type 2, Niemann Pick disease, sialidosis, galactosialidosis, arylsulfatase A pseudodeficiency, and some forms of ceroid lipofuscinosis, have been associated with myoclonic epilepsy (63,64). It is intriguing to speculate that these disorders could share a common abnormality related to lysosomal targeting or processing that contributes to this rare phenotype.…”
Section: Myoclonic Epilepsy In Gaucher Diseasementioning
confidence: 99%
“…Moreover, Philpot et al [1997], studying a group of patients with vascular dementia (VaD) and Alzheimer disease (AD), showed that brain DNA from a postmortem sample revealed the ASA pd mutation in 60% of VaD cases and 34% of AD cases; this percentage is higher than previous studies of culturally similar populations and the authors suggested that ASA pd may be a risk factor for dementia. This genetic variant, also found in other sporadic cases with different neurological conditions, such as Lafora disease [Tinuper et al, 1994] or postanoxic demyelination [Weinberger et al, 1994], has never been previously described in WD. Some authors hypothesized that ASA pd may play a role in modulating the severity and the evolution of an associated disease [Weinberger et al, 1994], as suggested for the apo-E allele and Alzheimer disease [Rubinstein et al, 1994], Parkinson disease [Rubinstein et al, 1994], and Creutzfeldt-Jacob disease [Roses et al, 1995].…”
Section: Discussionmentioning
confidence: 92%